O processo de ensino e aprendizagem da geometria: representações sociais de professores do 5.º ano do Ensino Fundamental - Stanich, Karina Alves Biasoli (2013)
This study is a part of a larger Project called Recurring Difficulties of the 5th grade Mathematics learners in elementary school which was developed during 2011 and 2012. The present study has brought together teachers of eighteen schools units from São Paulo/Brazil with the intent to understand the manner on how these teachers had identified and represented the difficulties of their students regarding the Geometry knowledge by using interviews with the groups of teachers as well as analyzing national curriculum documents with the support of the Social Representations Theory framework. The outcomes have shown a network of meanings, historically built and summarized in the following contexts: the absence of a minimum knowledge repertoire built by this group around geometry concepts and contents; negative categorization of geometry being considered abstract and inappropriate to be taught; presence of an essentially practical teaching; displacement of the goal in geometry teaching reduced to its practical application against the possibility of developing the capacity to represent and theoretically operate on daily life basis. The abstraction of geometry ceases to be a characteristic or a goal to be achieved by constituting itself as a negative emblem which justifies all actions for an essentially practical teaching